Necessary people : a novel - Pitoniak, Anna (Little, Brown and Company, 2019)
Stella and Violet are best friends, and from the moment they met in college, they knew their roles. Beautiful, privileged, and reckless Stella lives in the spotlight. Hardworking, laser-focused Violet stays behind the scenes, always ready to clean up the mess that Stella inevitable leaves in her wake. After graduation, Violet lands a job in cable news and works her way up from intern to producer. Stella, envious of Violet's new life, gets hired at the same network in front of the camera and becomes the face of all Violet's work. As Violet and Stella strive for success, each reveals how far she'll go to get what she wants -- even if it means destroying the other person along the way. -- adapted from jacket